2005
DOI: 10.1677/joe.1.06262
|View full text |Cite
|
Sign up to set email alerts
|

Gastric immunolocalization and plasma profiles of acyl-ghrelin in fasted and fasted-refed prepuberal gilts

Abstract: Ghrelin is a peripheral circulating hormone, mainly released from the stomach, which can stimulate food intake. We studied fed, fasted and fasted-refed prepuberal gilts in order to outline possible changes in gastric mucosal ghrelin cells and in plasma ghrelin profiles in reponse to food deprivation. Acyl-ghrelin-immunoreactive cells were numerous in oxyntic glands, less abundant in cardiac glands and least frequent in pyloric glands, with the addition of a minor population of labelled cells in the gastric pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
6
35
2
Order By: Relevance
“…It plays a crucial role in regulation of many biological functions like food intake, gastrointestinal motility, hormone secretion, glucose and enzymes release. In porcine stomach, ghrelin-immunoreactive cells are most abundant in oxyntic and cardiac glands while less numerous in pyloric glands (Govoni et al, 2005). On the other hand, Hayashida (2001) reported that immunoreactive cells are abundant in all gastric mucosal areas.…”
Section: Discussionmentioning
confidence: 98%
“…It plays a crucial role in regulation of many biological functions like food intake, gastrointestinal motility, hormone secretion, glucose and enzymes release. In porcine stomach, ghrelin-immunoreactive cells are most abundant in oxyntic and cardiac glands while less numerous in pyloric glands (Govoni et al, 2005). On the other hand, Hayashida (2001) reported that immunoreactive cells are abundant in all gastric mucosal areas.…”
Section: Discussionmentioning
confidence: 98%
“…In most mammals, ghrelin is mainly produced in the mucosa of the stomach fundus, where it is abundant in the oxyntic, pyloric and cardiac glands (Date et al 2000, Tomasetto et al 2000, Dornonville de la Cour et al 2001, Hayashida et al 2001, Rindi et al 2002, Govoni et al 2005. A recent study (Govoni et al 2005) in pigs has shown that ghrelin is most abundant in the oxyntic and cardiac glands and less numerous in the pyloric glands.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, in the present work, we could not assess whether an abnormal expression of GOAT in tumor tissue may account for the low levels of acyl ghrelin detected in our patients. The recent availability of antibodies directed against acyl ghrelin and GOAT (22,23), and adapted for immunohistochemical studies makes it possible to plan further studies to investigate the metabolism of ghrelin in endocrine tumor tissues.…”
Section: Discussionmentioning
confidence: 99%